A question of time and space: a model approach to the synchronous precipitation of gypsum and halite during the Messinian Salinity Crisis - R. M. Ebner; P. T. Meijer (Climate of the Past)
Salt giants, although well studied, still offer some unsolved questions. One example is the Messinian salt giant which formed during the Messinian Salinity Crisis in the Mediterranean Sea. While a common assumption is that gypsum precipitated in the marginal parts of the basin before halite formed in the deeper part of the basin, this could not yet be confirmed. Indeed, it has also been suggested that, while the primary lower gypsum was forming, the deep basin was already accumulating halite. In this study we use box modeling to investigate the distribution of halite and gypsum deposits for different possible configurations of the basin and circulation. Due to a dimensionless description of basin restriction, our results can be transferred to other basins. With this approach we find that under the right conditions all configurations lead to a simultaneous but spatially separated precipitation of gypsum and halite. They would, however, not lead to the spatial pattern that is observed in the Mediterranean, i.e., halite deposition in the deep basins, while gypsum is deposited in the marginal basin. Based on those results we propose a timeline for a salinifying basin. For an average salinity above gypsum but below halite saturation, halite is first formed in a sufficiently restricted marginal part, and only once the average salinity approaches halite saturation can it also form in the open basin due to horizontal salinity gradients. Once the whole basin has reached halite saturation, gypsum only forms in marginal basins with a positive local freshwater budget. Such a mechanism, however, would produce less than 1 m of gypsum within 25 000 years. We thus conclude that a simultaneous, yet spatially separated precipitation of gypsum and halite within one basin is possible but unlikely to have led to the massive primary lower gypsum outcrops in the Mediterranean, while halite formed in the deeper parts of the same sub-basin.